Atypical action updating in a dynamic environment associated with adolescent obsessive–compulsive disorder. (10th May 2022) - Marzuki, Aleya A.; Vaghi, Matilde M.; Conway‐Morris, Anna; Kaser, Muzaffer; Sule, Akeem; Apergis‐Schoute, Annemieke; Sahakian, Barbara J.; Robbins, Trevor W.
Abstract : Background: Computational research had determined that adults with obsessive–compulsive disorder (OCD) display heightened action updating in response to noise in the environment and neglect metacognitive information (such as confidence) when making decisions. These features are proposed to underlie patients' compulsions despite the knowledge they are irrational. Nonetheless, it is unclear whether this extends to adolescents with OCD as research in this population is lacking. Thus, this study aimed to investigate the interplay between action and confidence in adolescents with OCD. Methods: Twenty‐seven adolescents with OCD and 46 controls completed a predictive‐inference task, designed to probe how subjects' actions and confidence ratings fluctuate in response to unexpected outcomes. We investigated how subjects update actions in response to prediction errors (indexing mismatches between expectations and outcomes) and used parameters from a Bayesian model to predict how confidence and action evolve over time. Confidence–action association strength was assessed using a regression model. We also investigated the effects of serotonergic medication. Results: Adolescents with OCD showed significantly increased learning rates, particularly following small prediction errors. Results were driven primarily by unmedicated patients. Confidence ratings appeared equivalent between groups, although model‐based analysis revealed that patients' confidence was less affected by prediction errors compared to controls. Patients and controls did not differ in the extent to which they updated actions and confidence in tandem. Conclusions: Adolescents with OCD showed enhanced action adjustments, especially in the face of small prediction errors, consistent with previous research establishing 'just‐right' compulsions, enhanced error‐related negativity, and greater decision uncertainty in paediatric‐OCD. These tendencies were ameliorated in patients receiving serotonergic medication, emphasising the importance of early intervention in preventing disorder‐related cognitive deficits. Confidence ratings were equivalent between young patients and controls, mirroring findings in adult OCD research.